2018
DOI: 10.2147/ott.s158638
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-gene-based prognostic model predicts lung adenocarcinoma survival

Abstract: IntroductionLung adenocarcinoma (LAC) accounts for more than a half of non-small cell lung cancer with high morbidity and mortality. Progression of treatment has not accelerated the improvement of its prognosis. Hence, it is an urgent need to develop novel biomarkers for its early diagnosis and treatment.Materials and methodsIn this study, we proposed to identify LAC survival-related genes through comprehensive analysis of large-scale gene expression profiles. LAC gene expression data sets were obtained from T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 38 publications
0
36
1
Order By: Relevance
“…Zhao et al developed a TCGA-based model using 20 filtered genes that showed lower accuracy (61.5% vs. 67%) for predicting OS compared to ours. 43 Gao et al established a TCGA-based survival model using methylation-driven genes that was also inferior to ours (66% vs. 67%). 44 There were several limitations to our study.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Zhao et al developed a TCGA-based model using 20 filtered genes that showed lower accuracy (61.5% vs. 67%) for predicting OS compared to ours. 43 Gao et al established a TCGA-based survival model using methylation-driven genes that was also inferior to ours (66% vs. 67%). 44 There were several limitations to our study.…”
Section: Discussioncontrasting
confidence: 62%
“…Our study exhibits superiority over previous studies of survival prediction. Zhao et al developed a TCGA‐based model using 20 filtered genes that showed lower accuracy (61.5% vs. 67%) for predicting OS compared to ours . Gao et al established a TCGA‐based survival model using methylation‐driven genes that was also inferior to ours (66% vs. 67%) …”
Section: Discussionmentioning
confidence: 71%
“…Genetic expression analysis strongly correlates with prognosis, especially the 20-gene set (66), therefore, it may become the main prognostic asset in the nearest future requiring well equipped genetic laboratories and cost-effective procedures so that it can become a part of routine testing. If the cost of the procedure was reduced, for instance by devising a standardized kit, it could be successfully used to predict the clinical course of NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of the prognostic score, the authors compared the 20-gene set to a 4-gene set (FUT4, SLC25A42, IGFBP1 and KLHDC8B) and the compared 4-gene set turned out to be effective, yet, its capacity to predict the clinical course was much lower than in the 20-gene set. The 5-year survival in the high and low group was ~20 and 50%, respectively (66).…”
Section: Revision Of Novel Prognostic Factors In Lung Cancermentioning
confidence: 95%
“…However, for practitioners faced with the problem of analyzing high‐dimensional data, practical guidance is missing, which of these many methods to apply. Consequently, in most applications (Zhao, Li, & Tian, ; Wang, Teng, Li, Hu, Liu, & Zheng, ; Xia et al., ), simple Cox model–based strategies are used, possibly leading to suboptimal results.…”
Section: Introductionmentioning
confidence: 99%